Serovar diversity of Leptospira sp. infecting wild rodents in Sarawak, Malaysia - Lela, Suut; Azim Mazlan, M.N; Mohd Taha, Arif; Joseph Tau, Anak Katip; Nor Aliza, A.R; Haironi, Y (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Leptopsirosis is a zoonotic disease with global distribution and rodents, in particular rats, have been identified as the main reservoir host. A study was conducted to determine the prevalence of antibodies against Leptospira sp. in wild rodents caught in selected areas of Sibu, Sarikei and Kapit in Sarawak during the period of July 2011 to May 2014. In total, 241 sera samples were collected from rodents caught from these three administrative divisions in Sarawak. Ninety-eight rodents (40.7%) were positive with antibody titre >1:50 by microscopic agglutination test (MAT) against 13 out of 20 common local leptospiral serovars tested. Sera of rodents caught in Sibu, Kapit and Sarikei divisions were positive at 43.9%, 37.5% and 36.4%, respectively. The top five serovars detected were: Autumnalis (25.5%), Tarassovi (23.5%), Bataviae (15.3%), Hebdomadis (8.2%) and Celledoni (7.2%). The main species of rodent positive for antibodies against Leptopsira sp. were Sundamys muelleri (50.0%), Rattus rattus (37.5%), Callociurus notatus (35.6%) and Rattus exulans (32.6%). This study indicates that leptospiral antibodies are prevalent amongst wild rodents in central Sarawak, which could be translated as high leptospiral carriage. The close interaction that exists between the local community and the environment could potentially propagate the transmission of Leptospira sp. to human in these areas. This study also provided essential information about local circulating Leptospira serovars, which could be useful for eventual prevention measures in disease transmission